Communicating - Coursen, David; Thomas, John; ERIC Clearinghouse on Educational Management ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
Chapter 11 of a revised volume on school leadership, this chapter offers suggestions for administrators desiring to communicate more effectively with various groups within and outside the school. The most valuable business executives excel at giving employees timely feedback, accepting criticism without being defensive, speaking clearly and succinctly, expressing feelings and ideas openly, and being good listeners. These communication skills are as valued in educational organizations as they are in the business world. Meaningful communication is a two-way information-sharing process. To be effective communicators, administrators must be skilled at listening, asking questions, paraphrasing, agreeing and disagreeing, describing behavior and feelings, checking perceptions, and providing feedback. Improvement exercises are provided, along with the rationale for establishing positive in-school communication and basic principles for communicating with small groups and angry groups. Communication with the public is equally important. Pointers are provided for planning the public relations program, attending to informal messages, fostering two-way communications, handling the media, and conducting opinion surveys. Although communicating can be complex and even frustrating, there are rich rewards for administrator perseverance in this area. (MLH)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: OERI-R-86-0003.
ERIC Note: In "School Leadership: Handbook for Excellence" (EA 020 964). For first edition, see ED 209 736.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Responsibility; Administrator Role; Communication Skills; Communication (Thought Transfer); Elementary Secondary Education; Group Dynamics; Organizational Communication; Principals; Public Relations; School Community Relationship; ERIC Publications; Guides, Non-Classroom.